ChemInform Abstract: A Hard Oxide Semiconductor with a Direct and Narrow Bandgap and Switchable p—n Electrical Conduction. Issue 10 (March 2015) - Ovsyannikov, Sergey V.; Karkin, Alexander E.; Morozova, Natalia V.; Shchennikov, Vladimir V.; Bykova, Elena; Abakumov, Artem M.; Tsirlin, Alexander A.; Glazyrin, Konstantin V.; Dubrovinsky, Leonid
Abstract The optical and electronic transport properties of two high‐pressure manganese oxide polymorphs, perovskite‐type ξ‐Mn2O3 and marokite‐type γ‐Mn3O4 are investigated by NIR, optical absorption, and Raman spectroscopy, and electrical resistivity measurements.